SURG-14. DOES WAITING MATTER? HOW TIME FROM DIAGNOSTIC MRI TO SURGICAL RESECTION AFFECTS OUTCOMES IN NEWLY DIAGNOSED GLIOBLASTOMA. (11th November 2019) - Young, Jacob; Muster, Rachel; Chandra, Ankush; Morshed, Ramin; Aghi, Manish
Abstract: Surgical resection is standard of care for patients with lesions concerning for high-grade glioma on MRI scan. There is no consensus on the urgency of the procedure for patients with good clinical performance status. Treatment history and functional outcomes were collected retrospectively from the electronic medical record for 105 consecutive patients with newly diagnosed WHO Grade IV gliomas who underwent surgical resection at the University of California, San Francisco in 2014 and 2015 (41% female, average age = 61.25). Median preoperative KPS score was 80. Median wait time to surgery was 11 days after the initial MRI scan (range: 0–213 days). Mean tumor volume at the time of initial MRI scan was 29.0 cm 3 (SD = 26.1 cm 3 ), which did not significantly differ from the mean pre-operative tumor volume of 31.2 cm 3 (SD = 27.3 cm 3 ). In this retrospective cohort, patients with larger glioblastomas were taken to surgery more quickly. Patients who presented to the emergency room were more likely to wait less than 7 days (p < 0.001). Patients who waited less than 7 days had a larger initial and pre-operative tumor volume compared to patients who waited between 7–21 days and patients who waited over 21 days (p=< 0.001, p=< 0.001). Tumor growth occurred in 10% of patients who waited one week or less, 26% of patients who waited one to three weeks, and 55% of patients who waited over 3 weeks. Overall survival was not significantly affected by wait time until tumor resection (p=0.52). Additionally, Tumor growth was not associated with postoperative outcomes including postoperative KPS score, postoperative deficits, 3-month follow up KPS score, overall survival, and survival after surgery. In conclusion, longer wait time to surgery does not impact overall survival, pre-, and post-operative KPS, but the tumor is likely to grow in the interim.